Pelatihan Penggunaan Aplikasi Penjualan Hewan Ternak Yg Ada Di Kampung Kunyit Desa Tumpatan Nibung Untuk Peningkatan Pendapatan Ekonomi - Syahril, Efendi; Tamrin; Fauzan, Nurahmadi (Cattleya Darmaya Fortuna, 2024)
The augmentation of economic income in rural regions frequently presents itself as a multifaceted challenge. This article endeavors to proffer a resolution by proposing a training program on the utilization of a livestock sales application in Kampung Kunyit, Tumpatan Nibung Village. The research aims to augment the understanding and skills of the community in employing livestock sales application technology as a means of economic diversification. Rural areas often grapple with the intricate challenge of enhancing economic income, necessitating innovative solutions. This article addresses this challenge by proposing a comprehensive training initiative focused on the adoption of a livestock sales application within the context of Kampung Kunyit, situated in Tumpatan Nibung Village. The primary objective of this research is to elevate the community's comprehension and proficiency in harnessing livestock sales application technology, strategically positioned as a conduit for economic diversification.